The Effect Of NPL, LDR, And CAR On ROA With NIM As A Mediation Variable In Conventional Bank Listed On The Indonesian Stock Exchange (BEI) - Salsabila, Aura; Sujadi, Eko; Sarmigi, Elex (SEAN Institute, 2024)
This study aims to examine the influence of NPL, LDR, and CAR on ROA with NIM as a mediating variable. The population used in this research is all conventional banks in Indonesia listed on the IDX in 2022, totaling 140 banks. This study employs secondary data with a sample of 86 banks using purposive sampling method for sample selection. The analytical method used in this research is partial least square method, which is used to analyze the relationship between two or more variables. The results show that NPL does not influence NIM, while LDR significantly influences NIM, and CAR does not influence NIM. Furthermore, NPL significantly influences ROA, but LDR and CAR do not influence ROA, and NIM also does not influence ROA. This study also proves that NIM mediates the influence of NPL on ROA, and LDR does not influence ROA through NIM mediation, and NIM also cannot mediate the influence of CAR on ROA.